Taking stock: Impacts of 40 years of policy research at IFPRI - Hazell, Peter B. R.; Slade, Roger (International Food Policy Research Institute, 2016)
Marking IFPRI’s 40th year, this report draws on external sources of evidence to review the Institute’s policy influence and impact to date and provides recommendations to improve. The external evidence includes citations data, external program and management reviews commissioned by CGIAR, and a series of independently conducted impact assessment studies of many of IFPRI’s research programs and projects between 1995 and 2015. The report also reviews recommendations as to how IFPRI might improve its impact.